Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
19th International Symposium in Robot and Human Interactive Communication 2010
DOI: 10.1109/roman.2010.5598649
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Affect Space for robots to display emotional body language

Abstract: Original article can be found at: http://ieeexplore.ieee.org ???This material is presented to ensure timely dissemination of scholarly and technical work. Copyright and all rights therein are retained by authors or by other copyright holders. All persons copying this information are expected to adhere to the terms and constraints invoked by each author's copyright. In most cases, these works may not be reposted without the explicit permission of the copyright holder." ???Copyright IEEE. Personal use of this ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 10 publications
3
69
0
Order By: Relevance
“…Affective communication has also been shown to provide additional facets to robot behaviour, making the relationship between robot and child deeper and richer. For example, emotional pose recognition with the Nao robot is consistent (Beck, Canamero, & Bard, 2010), facilitating the use of emotional expression as a feedback channel that can be employed by the robot. Following from this general competence, it has been shown that an empathic or supportive robot is prefered to a non-affective agent by children, and that its use can possibly lead to increased performance, in both teaching scenarios (Saerbeck, Schut, Bartneck, & Janse, 2010), and peer-peer interactions (Leite, Castellano, Pereira, Martinho, & Paiva, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Affective communication has also been shown to provide additional facets to robot behaviour, making the relationship between robot and child deeper and richer. For example, emotional pose recognition with the Nao robot is consistent (Beck, Canamero, & Bard, 2010), facilitating the use of emotional expression as a feedback channel that can be employed by the robot. Following from this general competence, it has been shown that an empathic or supportive robot is prefered to a non-affective agent by children, and that its use can possibly lead to increased performance, in both teaching scenarios (Saerbeck, Schut, Bartneck, & Janse, 2010), and peer-peer interactions (Leite, Castellano, Pereira, Martinho, & Paiva, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally felt that robots have emerged into an era of 'weak' Artificial Intelligence (A.I.) where currently they can imitate humans without being independent [50]. Either through autonomous means, or extensive exhaustive programming, robots have the potential to better everyday life.…”
Section: 2applicationsmentioning
confidence: 99%
“…automatic communicative gestures) are evoked to accompany specific types of dialogue 4 project website http://aliz-e.org 5 http://www.aldebaran-robotics.com 6 http://opencv.willowgarage.com/wiki/ 7 http://www.acapela-group.com/ 8 http://openccg.sourceforge.net/ 9 http://www.cs.waikato.ac.nz/ml/weka/ 10 http://www.cs.cmu.edu/ ∼ javabayes/Home/ 11 Features for the Bayes net dialogue act recogniser: lastSystemDialogueAct, subtask, hasName, hasYes, hasNo, hasCorrect, hasIncorrect, hasRepeat, hasStop, hasContinue, hasAskMe, hasAskYou, hasAnswer, hasAnswers, hasIDontKnow, hasQuestion; where the first two are non-binary features and the rest are binary ones filled from speech recognition N-best hypotheses. acts (e.g., greetings, requests) as well as static key poses that display emotions such as anger, sadness, fear, happiness, excitement and pride [Beck et al 2010]. The following features summarize the capabilities of the interactive conversational robot used in our experiments:…”
Section: The Robot Dialogue Systemmentioning
confidence: 99%